Spatial and temporal patterns of diffuse attenuation coefficient in Guánica, Puerto Rico: 15 years after development of a watershed management plan - Guzmán-Morales, Alba L.; Armstrong, Roy A.; Cruz-Motta, Juan J.; Hernández, William J. (Frontiers in Remote Sensing, 2024)
Decreased water quality in coastal environments due to land alterations by human activities has caused stressed and degraded coral reefs worldwide. The consequences of decreased water quality are not limited to coral reefs but also affect the quality of people's lives by increasing the incidence of diseases, so areas highly impacted have been prioritized for management. The Guánica Bay Watershed Management Plan was developed to reduce the non-point sources of pollution that arrive at the bay and to protect adjacent coral reefs, however, 15 years have passed since its creation and management actions have not been evaluated. The purpose of this study was to evaluate the effectiveness of the management actions implemented in the Guánica Bay watershed. Therefore, the objective of this study was to describe temporal trends (2002-2008 and 2016-2022) of remotely sensed diffuse attenuation coefficient at 490 nm (Kd490), a water quality indicator, in one managed (Guánica Bay) and three non-managed (Guayanilla Bay, Descalabrado River, and Guanajibo River) estuaries in Southwestern Puerto Rico. This was achieved by integrating ocean-color satellite imagery from MERIS-Envisat and OLCI-Sentinel-3 sensors that were sampled using a beyond-Before-After-Control-Impact (beyond-BACI) approach. An additional oceanic site was selected to evaluate continuity between sensors estimates. The imagery was processed using SNAP to extract Kd490 values in the estuaries. The analysis for the beyond-BACI found significant differences between periods (before and after) but the changes were unique to each location within estuary. The lowest Kd490 values and variability within estuary was observed in Guánica (range 0.05 -0.1 m -1 ) and the highest Kd490 values were observed in Guayanilla (0.35 m -1 ). The southern estuaries showed similar temporal trends, all having a peak in 2018 and a trough in 2020. Kd490 did not decrease in Guánica after the implementation of management actions, which can be related to the passage of several hurricanes during the after period. Further analysis should be done as new data is available and after the implementation of the last management actions suggested in the plan.